A plain linear rule for fatigue analysis under natural loading considering the coupled fatigue and corrosion effect. (May 2019) - Calderon-Uriszar-Aldaca, I.; Briz, E.; Biezma, M.V.; Puente, I.
Highlights: Review of linear and non-linear rule approaches to coupled corrosion-fatigue damage. Non-linear approach suitable for coupled corrosion-fatigue processes. Linear-rule determination of acceleration factor for equivalent damage. Linear-rule for coupled corrosion-fatigue effect considering structural reliability. Demo-case upholds simplicity and suitability of a representative structural element. Abstract: Fatigue under variable amplitude loading is currently assessed by applying the Palmgren-Miner linear rule in structural standards. However, this linear rule is inadequate in natural scenarios with coupled fatigue and corrosion effects, because the coupled corrosion-fatigue process synergistically accelerates deterioration. In view of the absence of specifications for the coupled fatigue-corrosion effect in structural standards, the objective here is to develop a simple and practical correction factor that will ensure a conservative linear summation of damage, taking the corrosion-fatigue effect into account. The theoretical consistency and the feasibility of the new adapted rule are tested in a case study.